Mother, Father, Lover: A creative look at how relationships with influence future intimate relationships - Khanyile, Musawenkosi (WritingThreeSixty, 2018)
Inspired by the Object Relations perspective in Psychology, which posits that humans are relationship-seeking beings whose early relationships with primary caregivers’ influence future relationships, this paper demonstrates through the use of poetry how early relationships with parents shape future intimate relationships. The poetry used focuses on the dynamics in three different kinds of relationships, namely the relationship with the mother, the father, and ultimately the lover. These dynamics are observed in tandem to demonstrate how the way we function in intimate relationships is impacted by our past experiences f rom our relationships with parents.